2014
DOI: 10.1021/co500001u
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Benzo[4,5]imidazo[1,2-a]quinazoline Derivatives via Facile Transition-Metal-Free Tandem Process

Abstract: A one-pot transition metal-free method for synthesizing benzo[4,5]imidazo[1,2-a]quinazoline and imidazo[1,2-a]quinazoline derivatives has been developed. The approach is widely applicable to 2-fluoro-, 2-chloro-, 2-bromo- and 2-nitro-substituted aryl aldehyde and ketone substrates. The fluorescence properties of target compounds were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…First of all, these optimized conditions were applied for the conversion of various kinds of benzaldehydes reacting with 2-(1H-benzo[d]imidazol-2-yl)aniline 1 into the corresponding 6-aryl-5,6-dihydrobenzo [4,5]imidazo[1,2-c]quinazoline analogues 3a-l (Scheme 2; Table 2, entries 1-12). From the Table 2, it could be found that the reaction could be suitable for benzaldehydes bearing electron-withdrawing groups (such as halide and cyano group) or electron-donating groups (such as alkoxy group).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First of all, these optimized conditions were applied for the conversion of various kinds of benzaldehydes reacting with 2-(1H-benzo[d]imidazol-2-yl)aniline 1 into the corresponding 6-aryl-5,6-dihydrobenzo [4,5]imidazo[1,2-c]quinazoline analogues 3a-l (Scheme 2; Table 2, entries 1-12). From the Table 2, it could be found that the reaction could be suitable for benzaldehydes bearing electron-withdrawing groups (such as halide and cyano group) or electron-donating groups (such as alkoxy group).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that they were usually obtained by a condensation of 1H-benzo [d]imidazol-2-amine, aldehydes, and dimedone [3]; or 1H-benzo [d]imidazol-2-amine and 2-halogenated benzaldehydes [4]; or two-step reaction of isatoic anhydride, o-phenylenediamine, and aldehydes [5]. In addition, treatment of 2-(1H-benzo[d]imidazol-2-yl) aniline with various kinds of benzaldehydes also is a more efficient procedure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations